2023
DOI: 10.1021/acs.inorgchem.3c03079
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Highly Luminescent Silver Nanoclusters in the 13X Zeolite Enabled by Mg2+ Doping and Their Luminescence Tuning by Heating Temperature

Qianrui Li,
Jinping Yuan,
Di Zhao
et al.

Abstract: Zeolite-confined silver nanoclusters (Ag-zeolite) have aroused vast interest due to their remarkable luminescence. The countercations within a zeolite play critical roles in determining the luminescent properties of the resulting Ag-zeolite. We observed, in this work, that introducing Mg 2+ enabled the Ag-13X zeolite a stable and bright yellow emission with a high PLQY of 94.6%, the first report on the luminescence enhancement of the Ag-13X zeolite by Mg 2+ , to the best of our knowledge. The formation of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the synthesis process of the material, not only Ag NCs are formed in the pores and cages of zeolites, but also many non-emissive Ag NPs are formed on the surface of zeolites. 32,36 Interestingly, we observed that the zeolite modified by PEG400 is more likely to form larger and more uniformly dispersed Ag NPs when used as a scaffold to stabilize nanoclusters (Fig. 2A and D), which may be caused by the increased exchange capacity of silver ions.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In the synthesis process of the material, not only Ag NCs are formed in the pores and cages of zeolites, but also many non-emissive Ag NPs are formed on the surface of zeolites. 32,36 Interestingly, we observed that the zeolite modified by PEG400 is more likely to form larger and more uniformly dispersed Ag NPs when used as a scaffold to stabilize nanoclusters (Fig. 2A and D), which may be caused by the increased exchange capacity of silver ions.…”
Section: Resultsmentioning
confidence: 93%
“…28 In the subsequent publication, we reported controllable luminescence of silver-loaded composites by adjusting guest–host–guest interactions, such as changing counter-balancing ions, activating temperatures, and assisting with terephthalic acid (TPA). 28–32 However, to our knowledge, the influence of zeolite surface modification on the luminescence capabilities of Ag-NCL@zeolites is rarely reported.…”
Section: Introductionmentioning
confidence: 98%